Performance of compreg laminated bamboo/wood hybrid using phenolic-resin-treated strips as core layer - Ashaari, Zaidon; Lee, Seng Hua; Zahali, Muhamad Rapie (Springer Verlag, 2016)
Physical and mechanical properties of compreg laminated bamboo/wood hybrid using phenolic-resin-treated strips as core layer were investigated. Compreg laminates made from treated core layer revealed better properties than the untreated control samples. Compreg laminated wood showed lower properties compared to compreg laminated bamboo and bamboo/wood hybrid. Assembly orientation exerted great influence on the properties as parallel laminated samples showed better strength and dimensional stability.